The phase-curve signature of condensible water-rich atmospheres on slowly rotating tidally locked exoplanets - Ding, F; Pierrehumbert, RT (American Astronomical Society, 2020)
We use an idealized three-dimensional general circulation model to study condensible-rich atmospheres with an ineffective cold trap on slowly rotating tidally locked terrestrial planets. In particular, we show the climate dynamics in a thin and temperate atmosphere with condensible water vapor. The similarities between our thin and temperate atmosphere and the warm and thick atmosphere approaching the water vapor runaway greenhouse in previous works are discussed, including the reversal of the thermal emission between the day and night hemispheres. Different from the transit spectroscopy of water vapor that depends on the absolute amount of atmospheric water vapor, the contrast between the dayside and nightside thermal emission provides information regarding the relative ratio of water vapor to the background atmosphere as well as the atmospheric pressure near the substellar tropopause and the emission level on the nightside on potentially habitable worlds.